Comparative Study of the Mechanisms Underlying the Effects of Prohexadione-Calcium and Gibberellin on the Morphogenesis and Carbon Metabolism of Rice Seedlings Under NaCl Stress - Meiling Liu; Naijie Feng; Dianfeng Zheng; Fengyan Meng (Plants)
NaCl stress is one of the most serious forms of salt stress. Prohexadione–calcium (EA) is a plant growth regulator, and gibberellin (GA) is a plant hormone that regulates various plant developmental processes. In this experiment, Guanghong 3 and Huang Huazhan served as experimental rice (Overza sativa L.) varieties to study the effects of EA and GA on the growth of rice seedlings. The results revealed that NaCl treatment significantly inhibited plant growth and destroyed the balance of the carbon metabolism. The inhibition effect of NaCl stress on the growth and physiological metabolism of rice seedlings was alleviated by EA and GA, but the effects of EA and GA were slightly different. Compared with the NaCl treatment, the EA and GA treatments significantly increased the net photosynthetic rate, stem base width, and dry matter accumulation but had opposite effects on the plant height, with the GA treatment significantly increasing the plant height of rice seedlings. The EA treatment was superior to the GA treatment in improving the metabolic pathway efficiency of sucrose and starch in the leaves of rice seedlings. The soluble sugar content, sucrose content, fructose content, sucrose synthase activity, sucrose phosphate synthase activity, α-amylase activity, β-amylase activity, and starch phosphorylase activity increased with increasing NaCl stress time, and the changes in the starch content and acid invertase activity were the opposite. The max/min values were reached on the 13th day of NaCl stress.